If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 6x = 78 Solving 3 + 6x = 78 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6x = 78 + -3 Combine like terms: 3 + -3 = 0 0 + 6x = 78 + -3 6x = 78 + -3 Combine like terms: 78 + -3 = 75 6x = 75 Divide each side by '6'. x = 12.5 Simplifying x = 12.5
| 0.5*x^2-1.5*x-0.375=x | | n+5*n-6=21cm^2 | | 3-(x+4)= | | 3x+18-7x=20-17x+13x-2 | | (n+5)(n-6)=21 | | 7=15-2p | | 4x^2-15x+13=-7x+10 | | 4(5n+7)-3n=3(4n-9) | | ln(x+9)+ln(x-5)=2ln(x) | | -2y+5=9 | | 0.05(80)+0.8x=0.4(80+x) | | 4x+40=76 | | 8x-4=3x+21 | | 2(2x-5)=3(6x+3) | | 12-23c=7(9-c) | | -2n^2+7n-1=0 | | 4(t-7)+6=30 | | -25n+7=17 | | 3.6+6=-2+2z | | x^2+12x+60=0 | | 212-2x=43x+23 | | X^2+12x+12=0 | | 4g^2-12g+11=0 | | 11-10x=49-24x | | 6(x+3)=2(10-x) | | -4=2-9x | | 345= | | (x*6)+y=75 | | 11x+22=6+87 | | (x*6)+y=78 | | 3x^2-4x+9=0 | | 42k^2+36k-96=0 |